A method for preparing collagen graft materials - (:unkn) unknown (My University, 1996)
The aim of this research was to develop a method of local production of collagen graft materials which are presently imported. The following methods were used to produce collagen membrane and sponge from human placentas and rat tail tendons. Collagen type I was isolated from human placenta and rat tail tendon by acetic acid extraction and characterised by SDS-PAGE. The collagen sponge was prepared by dissolving the collagen in HCl. The resulting dispersion was poured into a glass container, freeze-dried and then cross-linked by immersion in glutaraldehyde solution. It was then washed with distilled water and freeze-dried again. The collagen membrane was also similarly prepared by dispersing lyophilized collagen in HCl but then mixed with glutaraldehyde, exposed to U.V. light and later air dried.
Keywords: Humans; Animals; Collagen; Rats; Placenta; Solubility; Freeze Drying; Membranes, Artificial; Methods; Tail